2004
DOI: 10.1158/0008-5472.can-04-2364
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 3020insC Alone Is Not Sufficient for Colorectal Cancer Predisposition

Abstract: Mutations in NOD2 have been shown to associate with increased susceptibility to Crohn's disease. A recent Polish study linked the truncating NOD2 3020insC variant with an increased risk of colorectal cancer (CRC) at an older age (>50 years) of disease onset, with an odds ratio of 2.23. We studied the possible contribution of the 3020insC variant to CRC risk in a series of 1,042 Finnish population-based patients from which 926 samples were successfully analyzed and in 348 anonymous cancer-free controls. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…Very low penetrance effects cannot be excluded without larger materials. If the data from the 4 previous studies [12][13][14][15] and this study is combined to increase the sample size, the mutation frequencies of R702W, G908R and 3020insC do not significantly differ between CRC patients and controls; R702W, p 5 0.17; G908R, p 5 0.12; 3020insC, p 5 0.06 (Table III). If data on all variants (R702W/G908R/3020insC) were pooled, a significant difference is observed between cases and controls (p 5 0.008).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Very low penetrance effects cannot be excluded without larger materials. If the data from the 4 previous studies [12][13][14][15] and this study is combined to increase the sample size, the mutation frequencies of R702W, G908R and 3020insC do not significantly differ between CRC patients and controls; R702W, p 5 0.17; G908R, p 5 0.12; 3020insC, p 5 0.06 (Table III). If data on all variants (R702W/G908R/3020insC) were pooled, a significant difference is observed between cases and controls (p 5 0.008).…”
Section: Discussionmentioning
confidence: 91%
“…14 In the current study we have extended our efforts to characterize NOD2 as a candidate susceptibility gene for CRC, and screened the R702W and the G908R variants in the same population-based series of 1,042 CRC patients, in addition to 508 healthy controls. On the basis of these studies, no significant differences in the frequencies of R702W, G908R and 3020insC between CRC patients and controls could be detected (Table I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurzawski et al [25] found that the presence of 3020insC mutation increased the risk of developing CRC by 2.23-fold in Polish patients with an older average age at diagnosis. This was however not confirmed in a Finnish study by Alhopuro et al [26]. Noteworthy, in the most recent Greek study, all three common variants were found to be associated with an increased risk for CRC (OR: 2.4-5.2) [27].…”
Section: Introductionmentioning
confidence: 79%
“…Among the IBD-related genes, the genetic variants of nucleotide oligomerization domain 2/caspase activating recruitment domain 15 (NOD2/CARD15) are the most extensively studied with respect to their association to CRC susceptibility, notwithstanding various conflicting findings among different populations (Alhopuro et al, 2004;Kurzawski et al, 2004;Papaconstantinou et al, 2005;Roberts et al, 2006;Lakatos et al, 2007;Szeliga et al, 2008). Therefore, in this study, we aimed to investigate the frequency of five genetic variants of NOD2/CARD15 and their potential association to CRC susceptibility in Malaysian patients.…”
Section: Introductionmentioning
confidence: 99%